Etanercept Prevents Decrease of Cochlear Blood Flow Dose-Dependently Caused by Tumor Necrosis Factor Alpha. (July 2013) - Ihler, Friedrich; Sharaf, Kariem; Bertlich, Mattis; Strieth, Sebastian; Reichel, Christoph A.; Berghaus, Alexander; Canis, Martin
Objectives: Tumor necrosis factor alpha (TNF-alpha) is a mediator of inflammation and microcirculation in the cochlea. This study aimed to quantify the effect of a local increase of TNF-alpha and study the effect of its interaction with etanercept on cochlear microcirculation. Methods: Cochlear lateral wall vessels were exposed surgically and assessed by intravital microscopy in guinea pigs in vivo. First, 24 animals were randomly distributed into 4 groups of 6 each. Exposed vessels were superfused repeatedly either with 1 of 3 different concentrations of TNF-alpha (5.0, 0.5, and 0.05 ng/mL) or with placebo (0.9% saline solution). Second, 12 animals were randomly distributed into 2 groups of 6 each. Vessels were pretreated with etanercept (1.0 μg/mL) or placebo (0.9% saline solution), and then treated by repeated superfusion with TNF-alpha (5.0 ng/mL). Results: TNF-alpha was shown to be effective in decreasing cochlear blood flow at a dose of 5.0 ng/mL (p < 0.01, analysis of variance on ranks). Lower concentrations or placebo treatment did not lead to significant changes. After pretreatment with etanercept, TNF-alpha at a dose of 5.0 ng/mL no longer led to a change in cochlear blood flow. Conclusions: The decreasing effect that TNF-alpha has on cochlear blood flow is dose-dependent. Etanercept abrogates this effect.